Allelopathic effects of Mimosa bimucronata (DC) OK. on cultivated species - Jacobi, Ubiratã S.; Ferreira, Alfredo G. (Pesquisa Agropecuaria Brasileira, 1991)
Mimosa bimucronata fruits, leaves fragments and aqueous extracts of the leaves were tested to the possible allelopathic effects on the seed germination and radicle growth of lettuce, rice, carrot, chicory, kale, cucumber, cabbage and tomato. The green or ripe fruits did not inhibit the germination but the green ones inhibited the radicle growth. Aqueous extracts of the dry leaves inhibited the germination of lettuce, carrot, chicory and tomato. The radicle growth was inhibited in the eight species tested, and the inhibition was proportional to concentration of the extracts.